PERANCANGAN SISTEM INFORMASI DISTRIBUSI AIR BERSIH DENGAN PENDEKATAN PROTOTYPE DEVELOPMENT LIFE CYCLE - Aji Setiawan; Adam Arif Budiman; Rimba Sianturi; Andriansyah Zakaria (Infotekmesin, 2019)
The distribution of air in the Klender Flats in East Jakarta is still not evenly distributed, so that some of the residents of the flat are increasingly lacking in water. Remembering water is the main need in everyday life. To overcome the problems that occur, a tool is made that can measure air flow and regulate the distribution of air using Arduino Uno. This tool uses a device consisting of a solenoid valve and a water flow sensor that is sent to Arduino Uno. water flow sensor will calculate the amount of air that has been used and after reaching the maximum capacity the solenoid valve will flow air distribution in accordance with the maximum capacity of each family head (KK). To implement the tool into the system, the writer uses C programming language and for websites using PHP. The use of water will be monitored every one hour and the system will send data to the database for retrieving necessary monitoring data on the website in graphical form.